UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-PAIR-SHARE (TPS) DALAM MATERI TEKANAN KELAS VIII SMPN I KALIS - Ampriyadi, Iwan (Universitas Tanjungpura, 2014)
The aim of this research is to find out the improvement of students learning output use cooperative learning teaching type think pair share (TPS). The form of research is the classroom action research consisting of two cycles with the steps of planning, action, observation and reflection. The subject of this research is students grade 8 of SMPN 1 Kalis. Quantitative data is taken from the pretest and postest, then is defined the average scores.Â The result of this research shows that there is an improvement of average of learning output is 33,75 in the first cycles and then the second cycles is 41,25. The increase of completion of the learning output is the first cycles is 90,63 %, while the second is 93,75 %. The observation result of the learning prosess showed that the students learning activities improved and it affected the students learning output. The learning process use cooperative learning model with think pair share type is expected to be used by physics teachers to teach. Keys word: Learning output students, Cooperative type Think-Pair-Share (TPS), Pressure.